DESAIN MOZAIK PADA BINGKAI BELAH KETUPAT DENGAN MOTIF FRAKTAL DAN KONSTRUKSINYA PADA MATLAB - Miftahur Roifah (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2019)
Mosaics are the artistic creations made from pieces of shape which are then arranged and affixed to a plane and designed using a tiling pattern with a basic pattern of geometric objects.. The progress of science and technology enables innovations especially after the invention of computers, one of which is fractals. Fractals are widely used in computer graphics to create amazing shapes. Mosaic designs can also be made with fractal concepts. The aims of this research are to get the procedure for mosaic design on circle and rhombus frames by hexagon and Pinwheel tiling with fractal motif. The research method covered the design of basic form for mosaic in the interior of circle and rhombus. Furthermore fill the basic form of mosaic wuth some fractal motif. The results of this research are the procedure to design some basic form of mosaic with the following steps. Firstly, divide the interior area of the circle and rhombus. Secondly, identify the symmetrical basic form. Thirdly, design the basic form of mosaic. Whereas procedure to fill the basic form of mosaic with fractal motif with the following steps. Firstly, choose the specify fractal motif. Secondly, fill the motif into each basic form. Thirdly, fill motif on the background. Then the final step is programmed the mosaics with Matlab 7 software.